Shoutai Pill Enhances Endometrial Receptivity in Controlled Ovarian Hyperstimulation Mice by Improving the In-Vivo Immune Environment - Liu, Ziping; Zhang, Jizhong; Li, Liming; Zhang, Tiane; Huang, Li; Yin, Qiaozhi (Combinatorial Chemistry & High Throughput Screening, 2025)
BackgroundThe Shoutai pill (STP) is a classic formulation in traditional Chinese medicine. Preliminary experimental observations from our study suggest that it is effective in enhancing endometrial receptivity. However, the underlying mechanisms by which STP influences endometrial receptivity remain to be elucidated.ObjectiveThe objective of this study is to investigate the effects and mechanisms of the STP formulation in enhancing endometrial receptivity in controlled ovarian hyperstimulation (COH) model mice.MethodsThe network pharmacology analysis identified target proteins associated with the reduction of endometrial receptivity by STP. The COH mouse model was established using the GnRHa+PMSG+HCG protocol. The levels of MHC-1 and MHC-2 in mouse serum were measured using the ELISA method, while the levels of IL-1β, IL-4, IL-10, IP-10, IL-1a, IL-2, IL-17, TNF-a, and IFN-y were measured using liquid chip technology.ResultsSTP exhibited a significant improvement in the immune environment of COH model mice. The major active components of STP were identified as beta-sitosterol and quercetin, among others. Furthermore, AKT1, VEGFA, and several immune factors, such as TNF, IFN, IL-1β, and IL-10, were identified as key targets for regulating endometrial receptivity. STP enhanced the expression of IL-10, IL-4, and IP-10 in the mice while reducing the expression levels of IL-2, IL-17, TNF-α, and IFN-γ in COH mice. These effects led to the modulation of early high expression of IL-1β and an improvement in endometrial receptivity.ConclusionThis study demonstrates that STP can modulate in-vivo immune factors throughout the COH process, subsequently restoring the immune equilibrium within the endometrium, thereby enhancing the endometrial receptivity in the COH model mice.
Keywords: network pharmacology